Accumulation of polychlorinated biphenyls in the ovaries of deep-sea chemosynthetic clam Phreagena okutanii - Ikuta, Tetsuro; Nomaki, Hidetaka; Nakajima, Ryota (Frontiers in Marine Science, 2024)
Polychlorinated biphenyls (PCBs) persistently pollute marine ecosystems even though their production has been discontinued decades ago. Deep-sea organisms have been shown to accumulate PCBs and other persistent organic compounds; however, the extent of contamination and its effects remain poorly understood. Here, we measured PCB concentrations in separated organs of non-feeding bivalve clams belonging to Phreagena, a taxon representative of deep-sea chemosynthetic ecosystems. The highest concentrations of PCBs were detected in the ovaries. We also examined surface sediments of the clam habitat and observed concentrations comparable to those in the sediments of the seas around Japan, including shallow waters. The results showed that PCBs from the environment penetrate Phreagena clams through the body surface and accumulate in the female reproductive system. This raises concerns about a potentially severe direct impact on the survival of vulnerable and highly endemic deep-sea chemosynthetic bivalves.